La modification constitutionnelle de 1987, la reconnaissance du Québec comme société distincte et la dualité linguistique du Canada - Woehrling, José (Les Cahiers de droit, 1988)
On June 3, 1987, the Prime Minister of Canada and the ten provincial premiers signed the 1987 Constitutional Accord in which they agreed to amend the Canadian Constitution in order to meet the Quebec government's conditions for adherence to the Constitution Act, 1982. The recognition of Canada's linguistic duality and of Quebec as a distinct society were among the constitutional amendments agreed upon. These clauses continue to spark controversy, with some commentators claiming that the terms used in the Accord are too ambiguous, while others argue that their insertion in the Constitution will give rise to politically undesirable results. The author considers the meaning of these clauses and presents an historical account of the notions of “duality” and “distinct society” by analyzing their essential elements. He argues that if governments have recognized duality in order to protect the official language minorities, the purpose of the clause dealing with the protection and promotion of Quebec's distinct society is to maintain and develop its Francophone character. Where these two objectives conflict, the clause in the Constitutional Accord recognizing Canada's linguistic duality will prevail. The Accord's potential impact on the division of legislative powers and the Canadian Charter of Rights and Freedoms are also examined. In the author's opinion, the division of powers will not be modified; however, the recognition of duality and of Quebec as a distinct society may limit the potentially centralizing effects of the Charter. On the other hand, by relying on the duality clause, the courts will be able — should they so desire — to give the Charter's language guarantees a broader interpretation than they have until now been accorded. The author concludes by considering the possible interplay between the linguistic duality and the distinct society clauses once they are entrenched, and the multiculturalism clause (section 27 of the Charter,).